THE BUSINESS PERSPECTIVES STRATEGY TOWARDS THE TKI (INDONESIAN MIGRANT WORKERS) MARKET - Haeryip Sihombing; Moh. Yuhazri Yaakob; Mochamad Safarudin (Journal of Indonesian Economy and Business (JIEB), 2011)
The business prospects and opportunities of the migrant workers’ (TKI) market are still wide open. This is shown by the year to year remittances incremental of TKI thatcorresponds to the beneficial opportunity of the business players to optimize their exploration of this market. In reality, the current efforts and strategy in this exploration,however, are still not utilised effectively in terms of competitive advantage. Therefore the initiative strategy towards product differentiation and innovation of the offered service should be explored and optimised based on the sustainable beneficial prospects for the business. As described briefly in this paper through a case of business innovation towards differentiation, the proposed strategies such as localization and two-sided markets are required for business organisations to unlock their product innovation strategies towards TKI (as their customer) through the innovative solution against the poverty.Keywords: TKI, remittance, poverty, differentiated, solution